Conversing with motion : the last supper - Goh, Nathanael Wee Kiat (2018)
Conversing with Motion attempts to communicate with the audience the idea of the work through movements in the work and of the audience. In this work, the focus is on the 12 disciples depicted in Leonardo Da Vinci’s The Last Supper. This installation aims to let the audience understand how the 12 very different characters can come together to create a harmony amongst themselves and also with the audience in the physical space.